A drupe dehusker - Shamsudin, Rosnah; Samsu Baharuddin, Azhari; Vincent Eddy, Christine Jamie (2014)
The present invention relates to a drupe dehusker comprising: an outer body (100) including: a lower body (101); an upper body (103); and a top cover (105); a peeling basket (201) with a peeling disc (203) located inside the outer body (100); a motor (301) to drive the peeling disc (203) with speed controller (303), wherein the motor (301) and the peeling disc (203) are mechanically connected via a shaft (305) and a feet (307); characterized in that drupes are dehusked through the operation of the peeling disc (203) and the peeling basket (201), wherein the surface of the peeling disc (203) and the peeling basket (201) further comprising perforated sharp edges.